The Effect of Job Satisfaction, Job Stress, and Compensation on Employee Turnover Intention of PT XYZ - Fitria Nurismi; Siti Sarah (Jurnal Mirai Management, 2023)
The problem of Turnover Intention is a serious issue for a company. Turnover Intention can hinder the company's operations. This is the purpose of this research to analyze the effect of Job Satisfaction, Job Stress, and Compensation on Turnover Intention of employees at PT XYZ. The population in this study were all employees of PT XYZ, totaling 45 employees. The sampling technique used I n this study is a saturated sample technique, where this method makes all members of the population to be sampled in this study, using multiple linear regression to test the hypothesis results. The data collection technique used in this research is through interviews and distributing questionnaires. The results showed that the variables of Job Satisfaction and Job Stress partially had a positive and significant effect on the Turnover Intention variable, while the Compensation variable partially had a negative and significant effect on the Turnover Intention variable. And there is a simultaneous significant influence on Turnover Intention.